Brief review of pathophysiological disorders as consequence of psychological stress - López-Naranjo, Francisco; Córdova-Moreno, Rebeca; Heyerdahl-Viau, Ivo (Interacciones, 2023)
Background: Psychological stress is a reaction to an unexpected situation that favours adaptation and response to the event. However, when psychological stress is chronic or very intense, it can induce changes in various systems and tissues, causing diseases or aggravating existing ones. Objective: To briefly analyse the pathophysiological conditions caused by psychological stress. Method: A narrative review of the scientific literature on pathophysiological conditions as a consequence of psychological stress was performed. Results: Psychological stress can induce various conditions at the gastrointestinal, immune and cardiovascular levels. This is mainly due to the neurobiological and endocrine response because when faced with a stressful stimulus, a deregulated release of glucocorticoids and catecholamines is generated, altering the normal physiology of the organism. Gastrointestinal disorders are mainly due to goblet cell dysfunction, resulting in intestinal hyperpermeability, inflammation and infection. Changes at the immune level lead to an increase in inflammatory responses but a decrease in the protective activities of the immune system. Finally, cardiovascular conditions include atherosclerosis, increased blood pressure and stroke. Conclusion: Psychological stress can induce real physiological pathologies and, in some cases, fatal ones. Some of the molecular mechanisms involved in these pathologies have already been studied and identified. Knowledge of these molecular mechanisms can help clinicians and therapists to improve the treatment and therapy of patients.